TWO METHODS FOR 3-AMINOCYCLOPENTANESPIRO-5- HYDANTOIN THIONATION - Marinov, Marin (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
This article presents two methods for 3-aminocyclopentanespiro-5-hydantoin thionation. These methods are based on the treatment of the titled compound with P4S10 or Lawesson’s reagent. The corresponding dithio-analogue was synthesized as a result of these interactions. The structure of the product obtained was verified by 1HNMR, 13C NMR and mass spectral data.